2020
DOI: 10.1002/cssc.201903496
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Methyl Levulinate into Biosurfactants and Biolubricants by Chemoselective Reductive Etherification with Fatty Alcohols

Abstract: Biomass‐derived surfactants with very good surface tension and critical micellar concentration properties were obtained by conversion of methyl levulinate into methyl 4‐alkoxypentanoates through reductive etherification with aliphatic alcohols. Among different bifunctional acid/metal catalysts best results were obtained with Pd on carbon bearing acid sites. The reaction occurred through the formation of an enol ether intermediate followed by hydrogenation. Pd in high‐density planes was the active hydrogenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…For (hemi)acetals containing at least one α‐H, loss of water or R 1 OH generates the corresponding enol ether intermediate, in equilibrium with an oxocarbenium ion, which is easily reduced to the desired ether (path a). In the case of carbonyl compounds with no α‐H, (hemi)acetal intermediates might undergo a direct hydrogenolysis to the corresponding ether derivative (path b) [1g,38b–d,f,g,i] . It has also been suggested that direct hydrogenolysis, and/or related pathways, can entail the formation of an oxocarbenium ion intermediate by protonation of the (hemi)acetal and subsequent water/R 1 OH release, followed by its catalytic reduction to give the desired ether (path b’) [25a,38a,c,g,39] …”
Section: Reductive Etherification Of Alcohols or Surrogates With Aldehydes/ketonesmentioning
confidence: 99%
“…For (hemi)acetals containing at least one α‐H, loss of water or R 1 OH generates the corresponding enol ether intermediate, in equilibrium with an oxocarbenium ion, which is easily reduced to the desired ether (path a). In the case of carbonyl compounds with no α‐H, (hemi)acetal intermediates might undergo a direct hydrogenolysis to the corresponding ether derivative (path b) [1g,38b–d,f,g,i] . It has also been suggested that direct hydrogenolysis, and/or related pathways, can entail the formation of an oxocarbenium ion intermediate by protonation of the (hemi)acetal and subsequent water/R 1 OH release, followed by its catalytic reduction to give the desired ether (path b’) [25a,38a,c,g,39] …”
Section: Reductive Etherification Of Alcohols or Surrogates With Aldehydes/ketonesmentioning
confidence: 99%
“…Levulinic acid has been used as an alternative fuel and as a reagent to produce chemicals such as γ‐valerolactone, succinic acid, butanone and 5‐nonanone [61–63] . In addition, methyl levulinate can be reacted with fatty alcohols in a reductive etherification process, in the presence of a Pd/C catalyst to synthesise biosurfactants and biolubricants [64] …”
Section: Sugarcanementioning
confidence: 99%
“…[61][62][63] In addition, methyl levulinate can be reacted with fatty alcohols in a reductive etherification process, in the presence of a Pd/C catalyst to synthesise biosurfactants and biolubricants. [64]…”
Section: -Hmf Conversion Into Monomers and Fuelsmentioning
confidence: 99%
“…Über Corma, Mitglied des Internationalen Beirats der Angewandten Chemie und Ehrenmitglied des Beirats von ChemCatChem , wurde hier zuletzt 2018 als Gewinner der Blaise‐Pascal‐Medaille in Chemie berichtet . Seine Gruppe stellte in ChemSusChem die Synthese von 5‐Hydroxymethylfurfural abgeleiteter Weichmacher und die Umwandlung von Lävulinsäuremethylester in biobasierte Tenside und Schmiermittel vor …”
Section: Ausgezeichnet …unclassified